Histologist's original opinion compared with multidisciplinary team in determining diagnosis in interstitial lung disease. Issue 3 (4th November 2016) - Burge, PS; Reynolds, J; Trotter, S; Burge, GA; Walters, G
Abstract : Guidelines recommend that multidisciplinary interstitial lung disease meeting (ILD MDT) decisions become the gold standard for diagnosis, replacing the histologist from this position, and identify this as requiring supportive evidence. We have compared diagnoses from lung biopsy material made by expert histologists with the subsequent consensus opinion from a properly constituted ILD MDT in 71 consecutive patients referred to a regional thoracic unit. MDT changed the original histological diagnoses in 30% (95% CI 19.3% to 41.6%) and strengthened the diagnoses from probable to confident in a further 17% (95% CI 9.1% to 27.7%). The assessment of hypersensitivity pneumonitis, non-necrotising granulomas and organising pneumonia accounted for the majority of the changes.